Analysis of Village Head Leadership Styles : (Case Study in Hegarmanah Village, Jatinangor District, Sumedang Regency) - Ramadhan, Ndaru; Nuraeni, Icha; Khotimah, Nur (Universitas Teknologi Surabaya, 2025)
The leadership style of a village head certainly influences the running of the government in a village. Therefore, analyzing the village head's leadership style is essential to determine the direction of village development for the community's welfare. This research, conducted in Hegarmanah Village, Jatinangor District, Sumedang Regency, West Java Province, used a qualitative approach with interviews, observations, and literature studies as data collection techniques. Results show that the Hegarmanah Village Head employs a participatory democratic leadership style, as seen in two-way communication and community involvement in decision-making. Since this study focuses solely on the Hegarmanah Village Head's leadership, future research can further explore different leadership styles through comparative studies with other village heads.